Kenya Economic Update, December 2010 : Kenya at the Tipping Point? - World Bank (Washington, DC, 2017)
Kenya may be at a "tipping point," the theme of the third Kenya economic update which has a special focus on the transformative impact of information and communication technology (ICT) and mobile money. Over the last decade, ICT has outperformed all others sectors growing at an average of 20 percent per year. The benefits of ICT are starting to be felt in other sectors, and have contributed to the conditions for Kenya to reach this tipping point. Kenya has entered the new decade with renewed and stronger than expected growth. The passing of the new constitution, continued strong macroeconomic policies, and a favorable regional environment have created a new positive economic momentum. Kenya may again be positioned to experience high growth. Over the last three decades Kenya has experienced only two short episodes when economic growth exceeded five percent and was sustained for at least three consecutive years: 1986-88, and 2004-2007. Is Kenya again at the verge of experiencing another growth spurt? Will it last longer and go deeper than the previous two episodes?